2021
DOI: 10.3390/nano11112890
|View full text |Cite
|
Sign up to set email alerts
|

Early Recognition of the PCL/Fibrous Carbon Nanocomposites Interaction with Osteoblast-like Cells by Raman Spectroscopy

Abstract: Poly(ε-caprolactone) (PCL) is a biocompatible resorbable material, but its use is limited due to the fact that it is characterized by the lack of cell adhesion to its surface. Various chemical and physical methods are described in the literature, as well as modifications with various nanoparticles aimed at giving it such surface properties that would positively affect cell adhesion. Nanomaterials, in the form of membranes, were obtained by the introduction of multi-walled carbon nanotubes (MWCNTs and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Simultaneously, the peaks at ~1342, ~1600 cm −1 for all SCF samples are apparent and not shown in the pristine SiC nw sample. Based on our previous work, it is demonstrated that they are caused by the disordered D-mode and ordered G-mode of carbon, respectively [29][30][31]. This means the core-shell structure may be reserved well after the growing process (Figure S1) of metal oxide, which can be proven by microstructure observation.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Simultaneously, the peaks at ~1342, ~1600 cm −1 for all SCF samples are apparent and not shown in the pristine SiC nw sample. Based on our previous work, it is demonstrated that they are caused by the disordered D-mode and ordered G-mode of carbon, respectively [29][30][31]. This means the core-shell structure may be reserved well after the growing process (Figure S1) of metal oxide, which can be proven by microstructure observation.…”
Section: Resultsmentioning
confidence: 70%
“…Simultaneously, the peaks at ~1342, ~1600 cm −1 for all SCF samples are apparent and not shown in the pristine SiCnw sample. Based on our previous work, it is demonstrated that they are caused by the disordered D-mode and ordered G-mode of carbon, respectively [29][30][31]. This means the Figure 2 shows that there are several Raman peaks for SCF samples, located at 680 cm −1 , 796 cm −1 , 973 cm −1 , ~1342 cm −1 , and ~1600 cm −1 .…”
Section: Resultsmentioning
confidence: 75%
“…CNTs are materials with known chemical, electrical, mechanical, and structural properties, while their combination with PCL improves the electrical conductivity of the resulting composite and induces bone healing ( Peidavosi et al, 2022 ). Carbon nanotubes are often used as imaging agents and carriers of bioactive molecules ( Saito et al, 2008 ; Gonçalves et al, 2016 ; Wesełucha-Birczyńska et al, 2021 ). Also, graphene is another ceramic material whose combination with PCL improves its processability, cell attachment, mechanical properties, biological function, and conductivity.…”
Section: Pcl-based Compositesmentioning
confidence: 99%
“…However, its application has some limitations due to the weak adhesion of cells on its surface. 135,136 To overcome its shortcomings, PCL nano synthesis materials, which are biodegradable, non-toxic, and stable, are often used in practical applications and have been shown to have different degrees of positive effects on the proliferation, viability, adhesion, and differentiation of various cells. [137][138][139] In the context of these studies, the application of PCL nanomaterials in repairing oral and maxillofacial tissue defects is also expected.…”
Section: Polycaprolactonementioning
confidence: 99%